Adolescent Sexual and Reproductive Health During the COVID-19 Pandemic: A Mini Review - Groenewald, Candice; Isaacs, Nazeema; Isaacs, Dane (Frontiers in Reproductive Health, 2022)
ABSTRACT This mini review explores the impact of the COVID-19 pandemic on adolescent sexual and reproductive health. We conducted a systematic rapid review of the literature across three databases, with a particular focus on the African continent. Few studies have specifically focused on adolescents in Africa and this paper contributes to this paucity of research. Findings revealed the unintended consequences of the pandemic. Studies across several countries showed that the respective lockdown measures restricted adolescents’ access to sexual and reproductive health services. The literature also showed increases in adolescent pregnancies during the lockdown, along with increases in reports of sexual violence against adolescents. We conclude this paper by offering recommendations to address these unintended consequences and potentially improve adolescent sexual and reproductive health in African communities.